2015
DOI: 10.1002/mnfr.201500449
|View full text |Cite
|
Sign up to set email alerts
|

G protein coupled receptor 18: A potential role for endocannabinoid signaling in metabolic dysfunction

Abstract: Endocannabinoids are products of dietary fatty acids that are modulated by an alteration in food intake levels. Overweight and obese individuals have substantially higher circulating levels of the arachidonic acid derived endocannabinoids, anandamide and 2-arachidonoyl glycerol, and show an altered pattern of cannabinoid receptor expression. These cannabinoid receptors are part of a large family of G protein coupled receptors (GPCRs). GPCRs are major therapeutic targets for various diseases within the cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 107 publications
(183 reference statements)
0
25
0
Order By: Relevance
“…In fact, IL-6 is one of the primary mediators of low-grade inflammation in obesity (3) and both CXCL-1 as well as IL-5 have been found to be altered in prediabetes (6,38). There are some evidence pointing at Abn-CBD as a modulator of the inflammatory response (19) and the two main G-protein coupled receptors (GPCRs) that so far have been related to Abn-CBD effects, i.e., GPR18 and GPR55, have been widely involved in inflammation and related processes (39,40). Comparable to our data, the GPR55 agonist O-1602 significantly reduced the levels of IL-6 both in plasma and pancreas tissue in mice with cerulein-induced pancreatitis (34).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, IL-6 is one of the primary mediators of low-grade inflammation in obesity (3) and both CXCL-1 as well as IL-5 have been found to be altered in prediabetes (6,38). There are some evidence pointing at Abn-CBD as a modulator of the inflammatory response (19) and the two main G-protein coupled receptors (GPCRs) that so far have been related to Abn-CBD effects, i.e., GPR18 and GPR55, have been widely involved in inflammation and related processes (39,40). Comparable to our data, the GPR55 agonist O-1602 significantly reduced the levels of IL-6 both in plasma and pancreas tissue in mice with cerulein-induced pancreatitis (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, Abn‐CBD induced increased [Ca 2+ ] i in islets from GPR55 −/− mice, consistent with the insulin secretion data and suggesting that it acts through another receptor. A possible candidate is GPR18, which is activated by Abn‐CBD, expressed by islets, and it has been reported that GPR18 activation is associated with transient elevation of [Ca 2+ ] i. Nothing is known about the functional role of GPR18 in islets, but it has been reported that the GPR18 agonist N‐arachidonylglycine promotes elevations in β‐cell [Ca 2+ ] i and potentiates insulin secretion from rat islets …”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider possible biased agonism for O-1918 at GPR18 because O-1918 increased calcium mobilization and mitogen activated protein kinase (MAPK) activity in GPR18-transfected HEK293 cells 31 . However, the possibility that these effects of O-1918 are tissue specific, reinforces the need for more studies to address this issue 32 .…”
Section: Discussionmentioning
confidence: 99%